PENGARUH HARGA & GAYA HIDUP TERHADAP MINAT BELI MASYARAKAT - PUJI MUNIARTY PUJI; Della Saputri; Aprianti; Devi Arisandi; Putri Wahyu Ikasanti; Tri Wahyuni (STEKOM PRESS, 2021)
The Influence of Prices and Lifestyle on People's Purchase Intention in Traditional Markets An Understood During the Covid-19 Pandemic. This study aims to determine the effect of prices and lifestyle on people's buying interest in understanding traditional markets during the Covid-19 pandemic. This type of research is a quantitative associative research and its location is in the traditional market An understand, Bima City. In this study, the sample consisted of 55 respondents who were selected using purposive sampling technique. Data collection techniques in this study using a questionnaire, observation, and literature study. Testing the instrument using the validity test and reliability test. The data analysis method used is multiple linear regression analysis, the coefficient of determination; f test (simultaneous test), t test (partial test) and classical assumption test. The results showed that by means of the t test (partial test) it is known that the price variable does not have a significant effect on the purchase intention variable while the lifestyle variable has a positive and significant effect on the purchase intention variable. Then by means of the f test (simultaneous test) it is known that the variable price and lifestyle variables have a positive and significant influence on the purchase intention variable.